Trades access common core. Line B, Employability skills, Competency B-3, Use interpersonal communication skills - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"No matter what your job is, you will need to communicate with other people. Your communication skills determine how successfully you receive and transmit information. Communication is arguably the most important of all life skills and plays a significant role in all aspects of work and home life. Communication is verbal, written, and non-verbal, and every gesture, voice inflection, or facial movement speaks volumes and conveys information to others. An effective communicator is also an active listener. Employers actively seek out Individuals who are good communicators. The following list of lines and competencies was generated with the goal of creating an entry-level trades training resource, while still offering the flexibility for lines to be used as stand-alone books. Line B - Employability Skills. B-1 Apply Study and Learning Skills, B-2 Describe Expectations and Responsibilities of Employers and Employees, B-3 Use Interpersonal Communication Skills, B-4 Describe the Apprenticeship System."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Interpersonal communication -- Textbooks; Employability -- Textbooks; Electronic books